Karakteristik Rumah Tangga Miskin Ektrem di Propinsi Jawa Barat - Suryadi, Dudi (Universitas Dr. Soetomo Surabaya, 2022)
This research is aim to determine the characteristics of extreme poverty and the factors that affect extreme poor households in West Java. The data used in this study is SUSENAS micro data for March 2020, published by BPS. The method used in this study is binary logistic regression. The independent variables in this study are household characteristics consisting of the number of household members, ownership of accident insurance, ownership of house certificates, and household's place of residence. Other independent variables related to the characteristics of the head of the household, consisting of the number of hours worked, age, education, marital status, gender, literacy, technology use and internet use. Meanwhile, the dependent variable is extreme poor households. Based on the results of the study, the number of household members, ownership of accident insurance, ownership of house certificates, household residence have an effect on extreme poverty. Therefore, to eradicate poverty, especially in West Java, through population control policies, providing social security, facilitating ownership of house asset certificates, as well as equitable development in rural areas. Meanwhile, the policy for alleviating extreme poverty according to the characteristics of the head of the household is to provide decent work, increase household capacity through education and training, and provide equal opportunities and rights for women to enter the labor market with appropriate wages.